The Hyksos Ruler Khyan and the Early Second Intermediate Period in Egypt: Problems and Priorities of Current Research Proceedings of the Workshop of the Austrian Archaeological Institute and the Oriental Institute of the University of Chicago, Vienna, July 4 - 5, 2014 - Forstner-Müller, Irene (Holzhausen, 2018)
Recent results from the most important sites of the Late Middle Kingdom and the Second Intermediate Period (Edfu, Tell el-Dab'a and Abydos) have broadened our knowledge of the situation in Egypt enormously. Of utmost importance in this context are the sealing impressions from Edfu and Tell el-Dab'a bearing the name of the Hyksos ruler Khyan and the discovery of the previously-unknown royal tombs of an independent "Abydene" Dynasty in Abydos, which bring new light to bear on our understanding of the political situation in this period. Besides King Apophis, Khyan is one of the most important kings of the 15th Dynasty. However, his chronological position within the 15th Dynasty is not clear. Traditionally he has been assigned to the middle of the 15th Dynasty, but recent results now indicate a dating at the beginning of the 15th Dynasty and an overlap between the 13th and the 15th Dynasty. This new chronological position has far-reaching consequences not only for Egyptian chronology, but also for the chronology of the Mediterranean world. The new finds from Tell el-Dab'a, Edfu and Abydos necessitate a revision of the chronology of Dynasties 13 to 17 in Egypt, and a reconsideration of political and administrative structures during the Second Intermediate Period. The discussions during the workshop were very positive, although a wide range of interpretations of the evidence still remain plausible, especially in respect of the chronological conclusions. These are reflected in the range of contributions to the volume. It is hoped that this publication will stimulate further discussion and research on this important topic.